2005
DOI: 10.1007/s11258-005-3788-0
|View full text |Cite
|
Sign up to set email alerts
|

Is Campanula glomerata Threatened by Competition of Expanding Grasses?

Abstract: In East Germany, a high percentage of species-rich, semi-natural dry grasslands has been converted into species-poor communities dominated either by Poa angustifolia or Festuca rupicola. The disappearance of low-intensity types of agricultural land-use such as mowing and grazing has been the cause for the decline of many grassland species, as lack of biomass extraction leads to a new situation in competition. Here we evaluate the performance of the rare forb Campanula glomerata in competition with P. angustifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 40 publications
4
22
1
Order By: Relevance
“…In contact with P. angustifolia, C. glomerata clearly experienced competition, which increased with density of the grass species in the mixture. These results are clearly in line with those of Bachmann et al (2005) in the first year performance of our study species. On the other hand, C. glomerata became facilitated in contact with F. rupicola in some years and competed in other years.…”
Section: Performance Of the Plant-plant Interactionssupporting
confidence: 92%
See 1 more Smart Citation
“…In contact with P. angustifolia, C. glomerata clearly experienced competition, which increased with density of the grass species in the mixture. These results are clearly in line with those of Bachmann et al (2005) in the first year performance of our study species. On the other hand, C. glomerata became facilitated in contact with F. rupicola in some years and competed in other years.…”
Section: Performance Of the Plant-plant Interactionssupporting
confidence: 92%
“…In order to evaluate effects of plant-plant interactions, we set up a competition experiment (replacement design, following De Wit 1960) between the aforementioned grass species and the rare and declining forb Campanula glomerata in 2002. Results of first-year performance (Bachmann et al 2005) demonstrated that responses of C. glomerata to the presence of grass species were species specific. In general, C. glomerata was facilitated by F. rupicola and outcompeted by P. angustifolia.…”
Section: Introductionmentioning
confidence: 99%
“…The encroachment of shrubs (e.g. Prunus spinosa, also noted in the phytocoenoses studied) is considered as the main factor for the decline in many herbaceous plant populations in communities from the Festuco-Brometea class [27,28]. The decrease in the abundance of flowering, combined with the effect of patch overgrowing, may also be influenced by fluctuations in environmental conditions, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…i) To explore the interaction among individual plants in the planting system, Relative Neighbor Effect (RNE) analysis was used based on equation from Markham and Chanway (1996) in Bachmann et al (2005), Oksanen et al (2006). RNE was calculated based on the sum of branches per plant and weight of kernel per plant per year, as follows:…”
Section: Nutmeg Plant Characteristicsmentioning
confidence: 99%